Deepening or buffering the crisis of social reproduction under capitalism? The case of digital care and domestic work platforms - Ivana Pais; Patrizia Zanoni (Labour & Law Issues)
This study investigates platform companies offering care and domestic services through the lens of social reproduction theory. This perspective embeds these platforms in capitalism by foregrounding the fundamental dependence of the capitalist economy on the paid and unpaid socially reproductive work largely carried out by women in the home, communities, welfare state services and the (informal) market. Such work does not only reproduce life, but also, by so doing, the labor-power necessary to generate value in the economy. Based on five cases of care and domestic services platform companies operating in Italy, the analysis reveals their roots in the current crisis of social reproduction, or the ability of individuals, households and societies to socially reproduce life, through adequate care and income. We show how this crisis manifests itself in multiple forms in the lives of platforms’ clients and workers, who are both largely women. While all platforms claim to be the solution to this crisis, their effects are not univocal. On the one hand, platforms that operate as mere digital intermediaries deepen the crisis of social reproduction by expanding informal work on a large scale. On the other hand, platforms that proactively set the terms of employment foster the recognition of care and domestic work and workers’ better protection. The study advances the extant literature by showing how, while care and domestic services platforms do not resolve the crisis of social reproduction, they might either deepen or buffer it. Their effects depend on how their business model and the related legal work status they offer to workers distribute costs, risks and value among workers and their households, customers, platforms themselves and the state. Distinct from legal perspectives, a social reproduction theory lens emphasizes how the different legal work statuses offered to care and domestic platform workers open up possibilities for their social struggles, whose outcomes however remain open-ended.